1997
DOI: 10.1136/oem.54.5.343
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Q16 questionnaire on neurotoxic symptoms and a review of its use.

Abstract: Objectives-The questionnaire 16 (Q16) is commonly used to study prevalences of neurotoxic symptoms among workers exposed to organic solvents. It has also been recommended that exposed workers reporting more than six symptoms should be referred for further examination of possible chronic toxic encephalopathy. It would be useful to know whether symptoms reported in the questionnaire also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 17 publications
2
65
2
3
Order By: Relevance
“…Although a higher number of symptoms were included in previous surveys, in the presented study, some symptoms which were found to be non-specific or autonomic (e.g. dizziness, headache, nausea, loss of appetite) were excluded, and therefore could not fall under any specific subscale [13,15,16,31]. Data from this study also provided identical findings to those presented by a large US Agricultural Health Study (AHS) on pesticideexposed male farmers [15].…”
Section: Discussionmentioning
confidence: 52%
“…Although a higher number of symptoms were included in previous surveys, in the presented study, some symptoms which were found to be non-specific or autonomic (e.g. dizziness, headache, nausea, loss of appetite) were excluded, and therefore could not fall under any specific subscale [13,15,16,31]. Data from this study also provided identical findings to those presented by a large US Agricultural Health Study (AHS) on pesticideexposed male farmers [15].…”
Section: Discussionmentioning
confidence: 52%
“…We conducted direct observations of non-industrial mining in order to analyze the hazards of this activity. Apart from this observation, because our survey aimed to outline the impact of the working conditions on the health of these mining craftsmen, we distributed a questionnaire based on a Swedish occupational health survey questionnaire [6]. Our survey took place from 22 December 2005 to 9 January 2006.…”
Section: Matherial and Methodsmentioning
confidence: 99%
“…Several types of neurologic endpoints are considered. Many studies have reported prevalence of a range of self-reported symptoms, often based on variations of an established checklist (189,123). Mood and affect have also been assessed using self-report as well as validated scales.…”
Section: Is Low-level Pesticide Exposure Neurotoxic?mentioning
confidence: 99%